Habitat Requirements of Breeding Scaled Quail in Texas - Rob R. Reid; Christian E. Grue; Nova J. Silvy (National Quail Symposium Proceedings, 2017)
Habitat variables were correlated with scaled quail (Callipep/,a squamata) whistle counts on 133 (24-km) random transects in Texas. Whether or not a particular habitat variable was correlated with whistle counts appeared to depend upon abundance and distribution of other habitat types and structural features. If >= 1 requisite for quail survival and reproduction (food, water, cover, nest sites) was limited, habitat types and structural features were usually positively correlated with whistle counts (P < 0.10). Conversely, abundant habitat types which did not provide all of these requisites were usually negatively correlated with whistle counts (P< 0.10). Correlations indicated breeding scaled quail selected the more dense, shorter shrub habitats. Mesquite (Prosopsis spp.) habitats were especially important to scaled quail in the Trans-Pecos region.
Keywords: breeding; Callipepla squamala; habitat; scaled quail; Texas